2018
DOI: 10.1103/physrevd.97.024007
|View full text |Cite
|
Sign up to set email alerts
|

Nonexotic matter wormholes in a trace of the energy-momentum tensor squared gravity

Abstract: Wormholes are tunnels connecting two different points in space-time. In Einstein's General Relativity theory, wormholes are expected to be filled by exotic matter, i.e., matter that does not satisfy the energy conditions and may have negative density. We propose, in this paper, the achievement of wormhole solutions with no need for exotic matter. In order to achieve so, we consider a gravity theory that starts from linear and quadratic terms on the trace of the energy-momentum tensor in the gravitational actio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(41 citation statements)
references
References 53 publications
0
41
0
Order By: Relevance
“…Furthermore, in our analysis we have obtained different numerical or relational constraints to the values of the m and n due to the existence conditions and physical features of the critical points corresponding to the second cosmological scenario. The energy-momentum squared gravity theory f (R, T 2 ) represents a recent proposal which takes into account the embeddedness of the energy-momentum squared scalar T 2 = T µν T µν and have been studied using different approaches [65,68,69,71,72]. Our study is based on the linear stability method and represents a complementary analysis of the energy-momentum squared gravity theory by investigating the phase space features and the stability properties of the critical points, associated to various cosmological epochs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in our analysis we have obtained different numerical or relational constraints to the values of the m and n due to the existence conditions and physical features of the critical points corresponding to the second cosmological scenario. The energy-momentum squared gravity theory f (R, T 2 ) represents a recent proposal which takes into account the embeddedness of the energy-momentum squared scalar T 2 = T µν T µν and have been studied using different approaches [65,68,69,71,72]. Our study is based on the linear stability method and represents a complementary analysis of the energy-momentum squared gravity theory by investigating the phase space features and the stability properties of the critical points, associated to various cosmological epochs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above they have discussed simple extensions to the anisotropic cosmology. Non exotic matter wormholes are studied in the framework of EMSG in [68]. Constraints on EMSG from neutron stars was studied in [69] and compact stars in the EMSG model were studied by Nari et al in [70].…”
Section: Introductionmentioning
confidence: 99%
“…In this work we shall work with f (R, T) gravity theory in which the Ricci scalar R is replaced with a suitable functional form of R and trace of energy momentum tensor T [43] and therefore is a straightforward conjecture to f (R) gravity (see [44,45]). f (R, T) gravity have proved to be successful in numerous cosmological sectors such as dark matter [46] dark energy [47], massive pulsars [48,49], super-Chandrasekhar white dwarfs [50], wormholes [51][52][53][54][55][56][57][58][59][60][61], gravitational waves [62][63][64], bouncing cosmology [65,66], baryogenesis [67,68], Big-Bang nucleosynthesis [69] and in varying speed of light scenarios [70]. The article is methodized as follows: In Section II we provide a summary of f (R, T) gravity and solve the field equations assuming a bulk viscous fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Nari and Roshan [16] studied physical viability and stability of compact stars in this framework. Morares and Sahoo [17] studied nonexotic matter wormholes while Akarsu [18] explored possible constraints from neutron stars in the same frame. Bahamonde et al [19] investigated the minimal and nonminimal coupling models of EMSG and observed that these models describe the current cosmic accelerated expansion.…”
Section: Introductionmentioning
confidence: 99%